A new Fenestrulina (Bryozoa, Cheilostomata) commensal with tube-dwelling anemones (Cnidaria, Ceriantharia) in the tropical southwestern Atlantic - Vieira, Leandro M.; Stampar, Sérgio Nascimento [UNESP] (Magnolia Press, 2014)
A new species of cheilostome bryozoan, Fenestrulina commensalis n. sp., was collected in December 2008 by scuba at 5-10 meters depth at Guaibura Beach, Guarapari, Esp rito Santo state, southeastern Brazil. The specimen was found associated with tubes of the cerianthid Pachycerianthus sp., representing the first commensal association between a bryozoan and a tube-dwelling anemone. Fenestrulina commensalis n. sp. is the third species of the genus found in Brazilian waters; it is distinguished from other Atlantic species of Fenestrulina by its small angular orificial condyles, a single oral spine and basal anchoring rhizoids arising from abfrontal pore chambers. Morphological adaptations to encrust the tubes of cerianthids include anchoring rootlets and weakly contiguous zooids. These morphological features allow the colony the flexibility to grow around the tube and feed relatively undisturbed by silt and detritus, being raised well above the softsediment substratum in which the tube-anemone grows.
Keywords: Association; Bryozoa; Cnidaria; Commensalism; Pachycerianthus; Fenestrulina; New species; Symbiosis; Cnidaria; Bryozoa; Taxonomia; Biogeografia; Biologia Marinha